The Effectiveness Of Judicial Duplication In Algerien Legislation - Slimani, Hindoun (Université de M'sila, 2020)
Developments and changes in the Algerian judicial system have strongly affected the authorities and the judicial bodies in terms of organization, functioning and competence. Thus, any development of the judicial system is systematically reflected through the rules of jurisdiction and each judicial reform brings new objective rules and new procedures relating to the judicial policy to be achieved to protect the acquired rights of individuals. The administrative courts are considered the cornerstone of the process of creating and concretizing duality in order to guarantee the litigant's right to resort to administrative justice. It is also considered to be the most important step in operating the duality system and thus adopts the principle of judicial specialization, which is one of the positive effects of legal duality.
Keywords: Judicial duplication - the principle of specialization of judges - administrative courts - conflict of jurisdiction.